2019
DOI: 10.1111/mec.14972
|View full text |Cite
|
Sign up to set email alerts
|

Multiple chromosomal rearrangements in a hybrid zone betweenLittorina saxatilisecotypes

Abstract: Both classical and recent studies suggest that chromosomal inversion polymorphisms are important in adaptation and speciation. However, biases in discovery and reporting of inversions make it difficult to assess their prevalence and biological importance. Here, we use an approach based on linkage disequilibrium among markers genotyped for samples collected across a transect between contrasting habitats to detect chromosomal rearrangements de novo. We report 17 polymorphic rearrangements in a single locality fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
189
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(214 citation statements)
references
References 76 publications
18
189
1
Order By: Relevance
“…Chromosomal inversions have frequently been implicated in promoting range expansions. For example, this has been empirically observed in species such as threespine stickleback (Gasteroseteus aculeatus; Jones et al 2012), yellow monkeyflower (Mimulus guttatus; Lowry and Willis 2010), rough periwinkle (Littorina saxatilis; Johannesson et al 2017;Westram et al 2018;Faria et al 2019) and red imported fire ant (Solenopsis invicta; Tsutsui and Suarez 2003;Wang et al 2013). Our results that are pertinent to reduced recombination in general, are likely to also be applicable to inversions.…”
Section: Discussionsupporting
confidence: 71%
“…Chromosomal inversions have frequently been implicated in promoting range expansions. For example, this has been empirically observed in species such as threespine stickleback (Gasteroseteus aculeatus; Jones et al 2012), yellow monkeyflower (Mimulus guttatus; Lowry and Willis 2010), rough periwinkle (Littorina saxatilis; Johannesson et al 2017;Westram et al 2018;Faria et al 2019) and red imported fire ant (Solenopsis invicta; Tsutsui and Suarez 2003;Wang et al 2013). Our results that are pertinent to reduced recombination in general, are likely to also be applicable to inversions.…”
Section: Discussionsupporting
confidence: 71%
“…LGC6.1/2, LGC14.1/2 and LGC17.1 (Faria, Chaube, et al, 2019a) that showed strong and consistent clines at the three study sites (A.M. Westram, R. Faria, K. Johannesson, R.K. Butlin, unpublished data). We calculated inversion heterozygosity as the proportion of the inversions that were heterokaryotypic in each female.…”
Section: Characterizing Female Hybrid Statusmentioning
confidence: 74%
“…Individuals that had genotype data for fewer than 50 SNPs after this filtering were excluded. We also considered the effect of genotype for each of five inversions LGC1.1, LGC2.1, LGC6.1/2, LGC14.1/2 and LGC17.1 (Faria, Chaube, et al, ) that showed strong and consistent clines at the three study sites (A.M. Westram, R. Faria, K. Johannesson, R.K. Butlin, unpublished data). We calculated inversion heterozygosity as the proportion of the inversions that were heterokaryotypic in each female.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, chromosomal inversions, which suppress recombination in heterozygotes, may facilitate adaptive divergence by maintaining sets of co-adapted alleles (18)(19)(20). Inversions can act as reservoirs of adaptive standing variation and as vehicles to redistribute adaptive variation by gene flow, thus promoting parallel divergence with a shared genetic basis (21)(22)(23)(24). On the other hand, inversions can confound inferences of the genetic basis of parallel divergence because they can modify apparent genetic sharing by capturing neutral loci within large haplotype blocks.…”
Section: Introductionmentioning
confidence: 99%